THE FINANCIAL DISTRESS ANALYSIS: PT. ASURANSI JIWASRAYA (PERSERO) CASE - Arifian Rachman, Andry (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the financial distress of PT. Asuransi Jiwasraya (Persero). The population in this study is the financial statements of PT. Asuransi Jiwasraya (Persero). The sampling technique uses purposive sampling and obtained financial statements in 2010–2017, which are currently gaining public attention. The data analysis method uses the Altman Z-Score III model. The analysis shows that companies tend to experience financial distress.